Obravnava pravopisa v treh predelavah Bohoričeve slovnice (1715, 1755, 1758) - Ahačič, Kozma (Slavistična revija, 2009)
The article examines the chapter on orthography in three revisions of Adam Bohorič's grammar (1584): Hipolit's from 1715, the manuscript revision from 1755, and the Klagenfurt revision from 1758. The analysis shows that, in termsof reliance on Bohorič, this is one of the most original chapter in all three revisions, with numerous original solutions, strongly marked by the spirit of the age. Particularly original is the part on "pronunciation with respect to the use of letters", dealing with issues that are also included in some linguistic introductions from the 17th and 18th cc., even if these introductions were not models for any of the revisions.
Keywords: 18.st.; Bohorič, Adam, ok. 1520-1598; grammar; Hipolit Novomeški, 1650-1722; history; jezikoslovje; linguistics; orthography; pravopis; Slovene; slovenščina; slovnice; zgodovina